Knowledge on Attention Deficit Hyperactivity Disorder Among School Teachers of Pokhara - Chapagain, Anushtha; Banstola, Ratna Shila; Shrestha, Romina; Banstola, Indira (Janapriya Journal of Interdisciplinary Studies, 2025)
Attention Deficit Hyperactivity Disorder (ADHD) is a neurodevelopmental condition that poses significant challenges on students’ academic performance and social integration. Teachers have important role in recognizing and supporting such children and parents. Therefore, necessitates an evaluation of their knowledge and understanding of the disorder. Study was aimed to assess the knowledge on ADHD among school teachers of Pokhara and find out the association between selected variables and the level of knowledge on ADHD. A cross-sectional survey was done. Study was conducted in 4 schools of Pokhara with the sample size of 110 school teachers teaching the basic level (1- 8 class), which was a complete enumeration sampling technique. Structured self-administered questionnaire was used for data collection and a standard tool ‘Knowledge on Attention Deficit Disorder Scale (KADDS)’ was used. The data was analyzed in SPSS 16 using descriptive statistical methods such as frequency, percentage, mean and standard deviation. Chi-square test was used to find out association between selected variables and the level of Knowledge. Findings revealed that 50.9% of teachers had adequate and 49.1% of teachers had inadequate knowledge on ADHD and mean knowledge score was 15.73±4.654 and maximum score was 32. There was statistically significant association between sex, teaching subject and experience of teachers in dealing with ADHD children and level of knowledge on ADHD (p<0.05). The study concluded that about half of the basic level school teachers had inadequate knowledge on ADHD, so that education/ training intervention related to ADHD can be provided to basic level school teachers.